KEMAMPUAN GURU DALAM PENATAAN LINGKUNGAN FISIK KELAS UNTUK MENINGKATKAN MINAT BELAJAR ANAK USIA DINI - Lesi Lesiani; Wicka Yunita Dwi Utami; Elenita Drihestyawati; Muhammad Zambri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The classroom learning environment plays an important role in supporting early childhood learning interests, especially when optimally designed and managed by teachers. This study aims to analyze the influence of teachers' abilities in arranging the physical classroom environment on early childhood learning interests. The study used a quantitative approach with simple linear regression data analysis. The research sample consisted of 16 children aged 4–5 years (TK A) at TKIT Muhtadi Land, Serang City. Data on teachers' abilities were obtained through questionnaires, while children's learning interests were collected through structured observations, learning assignment sheets, and school documentation. Data analysis was carried out using a prerequisite test, namely the normality test by looking at the Kolmogorov–Smirnov value, while hypothesis testing was carried out using simple linear regression analysis. The results of the hypothesis test showed a significance value of 0.011 (<0.05) with a coefficient of determination (R²) of 0.836. These findings indicate that teachers' abilities in arranging the physical classroom environment have a significant effect on early childhood learning interests, with a contribution of 83.6%, while the rest is influenced by other factors outside the study. Thus, improving teacher competence in managing the physical environment of the classroom needs to be an important concern in efforts to optimally foster interest in learning in early childhood.